Investigation of Tilt-Proprotor Loads Correlation Between Wind Tunnel Test Data and Comprehensive Modeling - Yin Ruan; Weite Wang; Wei Zhang (Aerospace)
The loads of a model tilt-proprotor with a gimbaled hub were measured in the wind tunnel of CHRDI, operating at 90°, 80°, 70°, 60°, and 45° inclination angles to represent the rotor loads of helicopter and transient flight modes. The flap, lead-lag moments, and pitch rod forces were measured. A comprehensive model was established with both linear inflow and free-wake non-linear inflow models. It is shown that there is a better correlation of alternating flap bending moments between test data and linear inflow model predicted values for the helicopter mode and a good correlation between measured data and free-wake predicted values for transition modes. The static moments are well captured by all inflow models at high thrust coefficients, while they fail to reflect the flap bending direction of the blade root at low thrust coefficients. Neither of the inflow models captured higher harmonics of the blade flap bending moments. The measured 2/rev harmonics of the lag bending moments lie between the linear inflow model and the free wake model predicted values. The current model with no dynamic stall model failed to capture the oscillating loads of the pitch rod.